The Effect of Technology Training on Increasing MSME Productivity: Case Analysis of Digital Training Programs for Local Craftsmen - Lukita, Chandra; Purnama, Ika Yuni; Rahardja, Untung; Natasya, Ersa Aura; Sanjaya, Yulia Putri Ayu (International Journal of Engineering, Science and Information Technology, 2025)
This research aims to explore the impact of technology training on increasing the productivity of micro, small and medium enterprises (MSMEs), focusing on local artisans. The Partial Least Squares structural analysis method (PLS-SEM) tests the proposed hypothesis based on survey data from MSMEs participating in digital training programs. The research results show that active participation in technology training programs significantly increases the application of technology in MSME business operations. Applying this technology will then have a positive impact on improving the productivity of MSMEs. Additionally, consistency in construct measurement, such as reliability and validity, is vital in explaining variation in the dependent variable. These findings provide an essential contribution to understanding the role of technology in increasing the productivity of MSMEs and highlight the importance of consistency in construct measurement in the context of this research.